Continuous intra-arterial blood gas monitoring for maintaining tissue perfusion during cardiopulmonary bypass (CPB) in cardiac surgery: A literature review - Sofa, Ibnu; Rahman, La Ode Abdul (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Heart surgery is the act of repairing or replacing part of the heart anatomy to restore the heart's function as a circulation pump. There are two categories of surgery, open heart surgery and closed heart surgery. Closed heart surgery does not require a cardiopulmonary bypass (CPB) machine. Meanwhile, open heart surgery will require support using a CPB machine to maintain circulation.Purpose: To provide an overview and ideas from the results of a literature review regarding the importance of blood gas monitoring in heart surgical procedures that use a cardiopulmonary bypass (CPB) machine or device.Method: Literature review research to analyze literature that has been selected from various sources to come to a conclusion on a new idea. The topics used are continuous blood gass and cardiopulmonary bypass. Journal searches via online databases include Scopus (n=310), Proquest (n=267), Sage journals (n=87), and Spinger link (n=20) so that the collected articles were 684. Researchers used a study selection guide PRISMA flow diagram for assessing article quality.Results: Based on a review of 10 selected journals, it was found that blood gas examinations and assessments carried out continuously can provide better and more accurate values. This is very useful in maintaining or maintaining the quality of blood in the body's circulation during surgery. Blood gas monitoring that is generally assessed is PH, PaO2, PCO2, lactate, electrolyte values, arterial saturation and venous saturation. The obstacle experienced by the public is that continuous blood gas examination devices are expensive.Conclusion: The use of blood gas monitoring and continuous blood gas measurements is very beneficial in improving the blood quality of patients undergoing heart surgery. Real time monitoring will be able to detect abnormal results and require immediate intervention. Keywords: Cardiopulmonary Bypass; Cardiac Surgery; Continuous Blood Gass. Pendahuluan: Tindakan pembedahan jantung adalah tindakan memperbaiki atau mengganti sebagian anatomi jantung untuk mengembalikan fungsi jantung sebagai pompa sirkulasi. Pelaksanaan pembedahan terdapat dua kategori, bedah jantung terbuka dan bedah jantung tertutup. Pada pembedahan jantung tertutup tidak memerlukan mesin cardiopulmonary bypass (CPB). Sementara bedah jantung terbuka akan memerlukan support penggunaan mesin CPB untuk mempertahankan sirkulasi tetap terjaga.Tujuan: Untuk memberikan gambaran dan gagasan dari hasil literature review tentang pentingnya monitoring gas darah dalam prosedur pembedahan jantung yang menggunakan mesin atau alat cardiopulmonary bypass (CPB).Metode: Penelitian literature review untuk menganalisis literatur-literatur yang telah dipilih dari berbagai sumber hingga menjadi sebuah satu kesimpulan ide baru. Topik yang digunakan yaitu continuous blood gass dan cardiopulmonary bypass. Penelusuran jurnal melalui online database antara lain, Scopus (n=310), Proquest (n=267), Sage journals (n=87), dan Spinger link (n=20) sehingga artikel yang terkumpul sebanyak 684. Peneliti menggunakan panduan penyeleksian studi PRISMA flow diagram untuk melakukan penilaian kualitas artikel.Hasil: Berdasarkan review 10 jurnal pilihan, didapatkan bahwa pemeriksaan dan penilaian gas darah yang dilakukan secara continuous dapat memberikan nilai yang lebih baik dan akurat. Hal ini sangat bermanfaat dalam menjaga atau mempertahankan kualitas darah dalam sirkulasi tubuh selama pembedahan berlangsung. Monitoring gas darah yang umumnya dinilai adalah PH, PaO2, PCO2, laktat, nilai elektrolit, saturasi arteri, dan saturasi vena. Kendala yang dialami oleh masyarakat adalah device pemeriksaan gas darah secara continuous memiliki harga yang mahal.Simpulan: Penggunaan monitoring gas darah dan pengukuran gas darah secara continuous sangat memberikan manfaat terhadap peningkatan kualitas darah pasien yang menjalani pembedahan jantung. Monitoring yang real time akan mampu mendeteksi hasil yang abnormal dan memerlukan intervensi segera. Kata kunci: Bedah Jantung; Continuous Blood Gass; Cardiopulmonary Bypass.